Religiosity and social problems in Malaysia - Md. Noon, Hazizan (IIUM Press, 2003)
This study analyzes the views of Malaysian teenagers on selected aspects of religion and its impact on their involvement in social problems. Religiosity is conceptualized as consisting of ideological, ritualistic, intellectual, experientiaL and consequential dimensions. It is measured in two ways: l) the overall measure of religiosity (for both Muslims and non Muslims which excludes ideological), and 2) the measure of religiosity for Muslims only (which includes ideological. The research, based upon a questionnaire administered to 2869 secondary school children, found that each component is positively correlated with the overall measure of religiosity. It also reveals that the more religious the person is, the less he or she becomes involved in social problems. Thus, religion plays an important role in contemporary Malaysian society and it should be given due emphasls in Malaysia's nation building and developmental activities.